Energy, exergy, energy matrices, exergoeconomic and enviroeconomic assessment of modified solar stills. (October 2021) - Pal, Piyush; Kumar Patel, Suresh; Bharti, Ajaya; Narayan, Audhesh; Dev, Rahul; Singh, Dhananjay
Highlights: Maximum thermal efficiency (34.63%) is obtained for modified double slope multi-wick solar still. Average annual exergy efficiency (2.579%) is obtained for modified single slope multi-wick solar still. Lower EBBT (0.637 years), higher EPF (1.568), and higher LCCE (0.2807) are found for modified double slope multi-wick solar still. Least CPL (₹ 0.48/kg≈₹ 0.76/kWh) and payback period (103 days) are estimated for modified double slope multi-wick solar still. Higher exergoeconomic parameter ( Rex ≈0.1140 kWh/₹) is found for modified single slope multi-wick solar still. Abstract: Passive solar stills globally accepted as a well-known system to desalinate unkempt water at a low yield rate without degradation of ecology and environment. Enhancement techniques are available to increase its productivity at higher capital and distillate production costs. Multi-wick solar stills can be a better option to increase productivity and alleviate distillate production cost relatively at lower capital cost. This work is allied to the assessment of the incorporation of hanging wicks in basin-type solar stills on overall performance improvement based on yield, energy, exergy, energy matrices, exergoeconomic, and enviroeconomic methodologies. Four modified solar stills, namely, modified basin type single slope solar still (MBSSSS); modified basin type double slope solar still (MBDSSS); modified basin type single slope multi–wick solar still (MBSSMWSS); and modified basin type double slope multi–wick solar still (MBDSMWSS) are designed and fabricated. Experimental observations are taken throughout the year at the climatic conditions of Prayagraj, India. Results revealed that the annual yield and exergy output; average annual energy and exergy efficiency of MBSSMWSS and MBDSMWSS (with black cotton wick (BCW)) are found as 1172.03 and 2583.99 kg; 100.70 and 97.36 kWh; 23.93% and 28.78%; 2.579% and 2.233%, respectively, in comparison to 861.55 and 1551.48 kg; 72.96 and 66.32 kWh; 15.08% and 17.48%; 1.765% and 1.160%, obtained for MBSSSS and MBDSSS, respectively. Based on energy and exergy, lower energy payback time; higher energy production factor; and higher life cycle conversion efficiency are found as 0.637 and 8.255 years; 1.568 and 0.121; 0.2807 and 0.0262 (life span of 50 years) for MBDSMWSS and MBSSMWSS, respectively, with BCW at lower water depth. Among the modified solar stills, minimum cost of distilled water, least payback period, higher CO2 reduction benefit and carbon credits (energy basis) are found for MBDSMWSS. The exergoeconomic parameter is found higher for MBSSMWSS.